2019
DOI: 10.1016/j.adro.2019.04.003
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 2 Randomized Pilot Study Comparing High-Dose-Rate Brachytherapy and Low-Dose-Rate Brachytherapy as Monotherapy in Localized Prostate Cancer

Abstract: PurposeTo compare health-related quality of life (HRQOL) of high-dose-rate brachytherapy (HDRB) versus low dose-rate brachytherapy (LDRB) for localized prostate cancer in a multi-institutional phase 2 randomized trial.Methods and MaterialsMen with favorable-risk prostate cancer were randomized between monotherapy brachytherapy with either Iodine-125 LDRB to 144 Gy or single-fraction Iridium-192 HDRB to 19 Gy. HRQOL and urinary toxicity were recorded at baseline and at 1, 3, 6, and 12 months using the Expanded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 61 publications
(128 reference statements)
2
23
0
Order By: Relevance
“…Acute urinary retention rate in our cohort was 2.4%, comparable with 1% to 20% reported in the literature. [11][12][13][14][15] Although the follow-up remained short, the estimated 3-year DFS and OS were also comparable with reported studies. 5 In the beginning, the procedure took about 3 hours to complete to meet dosimetric parameters of quality implantation.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Acute urinary retention rate in our cohort was 2.4%, comparable with 1% to 20% reported in the literature. [11][12][13][14][15] Although the follow-up remained short, the estimated 3-year DFS and OS were also comparable with reported studies. 5 In the beginning, the procedure took about 3 hours to complete to meet dosimetric parameters of quality implantation.…”
Section: Discussionsupporting
confidence: 85%
“…With its advantages of precise dosimetry, no radiation exposure to the providers and to a lesser degree to the patients compared with permanent seed implants, high-dose-rate (HDR) prostate brachytherapy offers a compelling alternative option. [9][10][11][12][13] Because HDR brachytherapy has been used to treat other malignancies, especially gynecologic cancers, many institutions have an HDR program. Expanding its role to prostate cancer treatment maximizes the usage of existing resources, thus reducing the overall cost of maintaining an active HDR program.…”
Section: Introductionmentioning
confidence: 99%
“…HDR-BT treated more advanced cases than LDR-BT in our cohort. Several retrospective studies 14 16 and a few preliminary and premature prospective studies have reported benefits of HDR-BT 17 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Two randomized controlled trials compared urinary quality of life between I-125 brachytherapy and single fraction HDR monotherapy (19-21 Gy x 1) (Table A ( 58 ). In another trial of 100 patients from Agoston et al , LDR brachytherapy was associated with greater IPSS scores at 3 months, but not at 12 months ( 59 ).…”
Section: Brachytherapy Monotherapy and Quality Of Lifementioning
confidence: 99%